Imparare a guardare. Luisa Bonesio racconta come il Villaggio Morelli a Sondalo sia opportunità di turismo colto - Maino, Elisabetta (Ri-Vista. Research for landscape architecture, 2015)
Heritages of exceptional value are often not properly understood, even if they are part of our everyday life. This is the case of the Eugenio Morelli sanatorium village. The experience of a research group, of which Luisa Bonesio is part, shows how those places can be “viewed consciously” through a cultural path, where “experts” and “inhabitants” mutually interact and exchange their own experiences, thus broadening knowledge from the local to the international level. Photographs drive this renewed wise and educated perception, and create a sort of touristic itinerary within the ex sanatorium, inviting to take a tour, and giving new life to things of the past, since new eyes now can see them.